ASUHAN GIZI MALNUTRISI, KURANGNYA PENGETAHUAN PADA PASIEN HENOCH SCHONLEIN PURPURA (HSP) DI RUANG ASAL 6 RSUD AL IHSAN PROVINSI JAWA BARAT - Ati Agustina Antares; Maryati Dewi; Jedya Lucas Atemalem Purba Purba; Mamat Rahmat; Widi Hastuti (Jurnal Gizi dan Dietetik, 2022)
Background : The epidemiology of HSP disease in Indonesia is still not clearly known. Research conducted at Cipto Mangunkusumo Hospital, Jakarta, showed a tendency to increase problems during 2006 compared to the number in the previous 5 years. HSP is not contagious and tends to be felt by children under 10 years of age1. Henoch-Schonlein purpura (HSP) is a red or purple-colored rash on the skin due to infection of the blood vessels in the skin, joints, intestines and kidneys. Immunity problems in patients with HSP are predicted to be caused by food, drugs, cold weather or insect bites. Severe HSP can cause complications, so treatment must be attempted intensively in a hospital. If the intestine is folded or damaged, the patient with HSP must try surgery. Case : A child patients with Henoch-Schonlein purpura (HSP), 7 years and 5 month old with nutrition diagnosis pediatric malnutritioan and lack of knowledge. Disscussion : Nutrition intervention with low fiber low fat served with variation and given depends on the ability to consume of the patient to improve outcome. Collaboration with the doctor has been done to everey treatment that was done. Education given to improve the family and the patient’s understanding along with motivation to maintain health post hospital care.Result : The intervention provided can improve nutritional problems in HSP patients.